The opioid peptide beta‐endorphin stimulates acrosome reaction in human spermatozoa. (11th December 2015) - Urizar‐Arenaza, I.; Estomba, H.; Muñoa‐Hoyos, I.; Matorras, R.; Esposito, A.; Candenas, L.; Pinto, F. M.; Valdivia, A.; Irazusta, J.; Subirán, N.
Summary: The acrosome reaction occurs in vivo following sperm capacitation and is essential for the acquisition of sperm fertilization ability. However, little is known about the molecular identity of the physiological acrosome reaction regulators. In addition to progesterone, which is produced by cumulus oophorus cells and known to regulate acrosome reaction by activating the specific calcium channel CatSper, endogenous opioid peptides such as beta‐endorphin and met‐enkephalin are present at high concentrations in the follicular fluid suggesting that the opioid system may be involved in the mechanisms regulating the acrosome reaction in humans. By using Reverse Transcription‐PCR, western blot and immunofluorescence approaches, we described the presence and localization of the beta‐endorphin precursor, pro‐opiomelanocortinin the middle section and in flagellum of human spermatozoa, and inside the seminiferous tubules of human testis. Flow cytometry and intracellular calcium analyses showed that beta‐endorphin causes an inversely dose‐dependent increase in the percentage of acrosome‐reacted sperm cells by a calcium‐independent protein kinase C pathway. These findings are important for future studies of sperm physiology and provide new insight into the function of the opioid system as a target of fertility management.